2010
DOI: 10.1042/bj20100890
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of monocarboxylate transporter 2 (MCT2) by AR-C155858 is modulated by the associated ancillary protein

Abstract: In mammalian cells, MCTs (monocarboxylate transporters) require association with an ancillary protein to enable plasma membrane expression of the active transporter. Basigin is the preferred binding partner for MCT1, MCT3 and MCT4, and embigin for MCT2. In rat and rabbit erythrocytes, MCT1 is associated with embigin and basigin respectively, but its sensitivity to inhibition by AR-C155858 was found to be identical. Using RT (reverse transcription)–PCR, we have shown that Xenopus laevis oocytes contain endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 42 publications
3
83
0
Order By: Relevance
“…Furthermore, studies indicate that these chaperones, both glycoproteins containing a single transmembrane domain with a short C terminus located in the cytosol and immunoglobulin-like domains in the extracellular region (43), remain tightly associated with the transporter in the membrane and are also involved in regulation/modulation of inhibitor sensitivity (9,10,41,42,44). In X. laevis oocytes, CD147 is endogenously expressed, whereas GP70, the preferred ancillary protein of MCT2, is not (9). These observations are confirmed by our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies indicate that these chaperones, both glycoproteins containing a single transmembrane domain with a short C terminus located in the cytosol and immunoglobulin-like domains in the extracellular region (43), remain tightly associated with the transporter in the membrane and are also involved in regulation/modulation of inhibitor sensitivity (9,10,41,42,44). In X. laevis oocytes, CD147 is endogenously expressed, whereas GP70, the preferred ancillary protein of MCT2, is not (9). These observations are confirmed by our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes-It has been shown that functional expression of MCT2 requires the ancillary protein GP70, which is not endogenously expressed in Xenopus oocytes (9,10). To examine the need of GP70 for proper expression of MCT2, we either expressed MCT2 alone or together with GP70 in Xenopus oocytes.…”
Section: Gp70 Is Required For Efficient Expression Of Mct2 In Xenopusmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable, and exploitable, feature of MCT transporters is that cochaperone immunoglobulin-family single-membrane pass proteins are required for their transport to the surface of the cell membrane. Specifically, MCT1, MCT3, and MCT4 bind to CD147 (also known as basigin, EMMRIN, and OX-47), which is required for their expression on the cell surface, whereas MCT2 binds and requires embigin for cell surface expression (60,61). Notably, the expression of CD147 on the cell surface also depends on co-expression with an MCT protein, and this interaction stabilizes both binding partners (62).…”
Section: Figurementioning
confidence: 99%
“…Oocytes were injected with 20 ng of the relevant cRNA. Oocytes to express MCT2 were injected with a mixture of 10 ng cRNA encoding MCT2 and 10 ng cRNA encoding the ancillary protein embigin (Ovens et al, 2010b). Control oocytes were injected with the equivalent volume of water (36.8 nl).…”
Section: Methodsmentioning
confidence: 99%